Augustine on memory - Grove, Kevin (Oxford stu in historical theology, 2021)
"Augustine of Hippo, indisputably one of the most important figures for the study of memory, is credited with establishing memory as the inner source of selfhood and locus of the search for God. Yet, those who study memory in Augustine have never before taken into account his preaching. His sermons are the sources of memory's greatest development for Augustine. In Augustine's preaching, especially on the Psalms, the interior gives way to communal exterior. Both the self and search for God are re-established in a shared Christological identity and the communal labors of remembering and forgetting. This book opens with Augustine's early works and Confessions as the beginning of memory and concludes with Augustine's Trinity and preaching on Psalm 50 as the end of memory. The heart of the book, the work of memory, sets forth how ongoing remembering and forgetting in Christ are for Augustine are foundational to the life of grace. To that end, Augustine and his congregants go leaping in memory together, keep festival with abiding traces, and become forgetful runners like St. Paul. Remembering and forgetting in Christ, the ongoing work of memory, prove for Augustine to be actions of reconciliation of the distended experiences of human life-of praising and groaning, laboring and resting, solitude and communion. Augustine on Memory presents this new communal and Christological paradigm not only for Augustinian studies, but also for theologians, philosophers, ethicists, and interdisciplinary scholars of memory"--